Use of artificial neural networks for prediction of discharge coefficient of triangular labyrinth side weir in curved channels - Bilhan, Omer; Emiroglu, M. Emin; Kisi, Ozgur (Elsevier Sci Ltd, 2011)
Side weirs have been extensively used in hydraulic and environmental engineering applications. The discharge coefficient of the triangular labyrinth side weirs is 1.5-4.5 times higher than that of rectangular side weirs. This study aims to estimate the discharge coefficient (C-d) of triangular labyrinth side weir in curved channel by using artificial neural networks (ANN). In this study, 7963 laboratory test results are used for determining the Cd. The performance of the ANN model is compared with multiple nonlinear and linear regression models. Root mean square errors (RMSE), mean absolute errors (MAE) and correlation coefficient (R) statistics are used as comparing criteria for the evaluation of the models' performances. Based on the comparisons, it was found that the neural computing technique could be employed successfully in modeling discharge coefficient from the available experimental data. There were good agreements between the measured values and the values obtained using the ANN model. It was found that the ANN model with RMSE of 0.1658 in validation stage is superior in estimation of discharge coefficient than the multiple nonlinear and linear regression models with RMSE of 0.2054 and 0.2926, respectively. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Side weir; Discharge coefficient; Labyrinth; Curved channel; Neural networks; Hydraulic